C-Tb Skin Test: A Step Toward Tuberculosis Eradication - Harshini T Reddy; Bhaskar Shenoy (Pediatric Infectious Disease)
C-Tb is a novel diagnostic test for latent tuberculosis (TB) infection. It is a skin test based on the principle of tuberculin skin test containing early secreted antigenic target 6 (ESAT-6) and culture filtrate protein 10 (CFP-10). It is important to understand newer diagnostics for TB in order to move towards the goal of eradication of TB. This test helps in early diagnosis and treatment of latent TB infection in high-risk individuals who can develop active TB. It is field-friendly and cost-effective, which comes with the ease of tuberculin skin test and the accuracy of interferon γ-release assay (IGRA).